2018
DOI: 10.5005/jp-journals-10085-7217
|View full text |Cite
|
Sign up to set email alerts
|

F - 07: Effectiveness of Ict Based Teaching Programme on Knowledge and Attitude Regarding Pubertal Health Among Girls of Pre Pubertal Age Group of 9-14 Years in Selected Schools at Puducherry

Abstract: Introduction: Pre adolescences is the period of human development just proceeding adolescence, specifically the period between approximate age of 9 and 12 years. .Girls attain reproductive maturity about 4 years after the first physical changes of puberty appear. It is a period of development of secondary sexual characteristics. The young girls are not improved psychologically to have the basic knowledge about the pubertal health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…31,32 The e-modules developed to address Adolescent Reproductive Health have been found to be effective in creating awareness among students of upper primary classes in Haryana. The results are in conjunction with studies of Lavanya S, 33 Phulambrikar RM, 34 Calabrese S, 24 Roberto AJ et al 20 and Singh S et al, 35 who reported the effectiveness of digital interventions to address reproductive and sexual health in classrooms. However, the findings of the study are antagonistic to the studies by Calise TV et al 36 and Gustina E & Wibowo M 37 who reported no change in knowledge regarding reproductive health post-intervention.…”
Section: Discussionsupporting
confidence: 74%
“…31,32 The e-modules developed to address Adolescent Reproductive Health have been found to be effective in creating awareness among students of upper primary classes in Haryana. The results are in conjunction with studies of Lavanya S, 33 Phulambrikar RM, 34 Calabrese S, 24 Roberto AJ et al 20 and Singh S et al, 35 who reported the effectiveness of digital interventions to address reproductive and sexual health in classrooms. However, the findings of the study are antagonistic to the studies by Calise TV et al 36 and Gustina E & Wibowo M 37 who reported no change in knowledge regarding reproductive health post-intervention.…”
Section: Discussionsupporting
confidence: 74%